2018
DOI: 10.1002/app.47377
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate)‐functionalized reduced graphene oxide‐based core–shell structured beads for thermally conductive epoxy composites

Abstract: Thermally conductive epoxy nanocomposite with core-shell structured filler beads has been prepared. The core represents plasma-treated poly(methyl methacrylate) bead, and the shell, amine-functionalized reduced graphene oxide (frGO) sheets. The negatively charged core and the positively charged shell form core-shell unified structure through electrostatic attraction and the conductive bridges are formed among neighboring filler particles in the composite mass. The epoxy composite prepared with these core-shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Figure 3 shows the intensity of light scattering as a function of the zeta potential of GO, BT@ZnPc-1 and BT@ZnPc-1 after modified by Ca 2+ particles at pH = 7. Zeta potential refers to the potential of the Shear Plane, which is related to the total charge carried by the particles in a particular medium and the peak of the zeta potential represents the type and intensity of charge present after dispersed in solution [23]. It can clearly be seen that the highest light scattering of GO is observed at the zeta potential of −17.29 mV, which is mainly owing to the ionization of oxygenated functional groups in a high polar solvent like water, and the pristine GO would assume slightly negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the intensity of light scattering as a function of the zeta potential of GO, BT@ZnPc-1 and BT@ZnPc-1 after modified by Ca 2+ particles at pH = 7. Zeta potential refers to the potential of the Shear Plane, which is related to the total charge carried by the particles in a particular medium and the peak of the zeta potential represents the type and intensity of charge present after dispersed in solution [23]. It can clearly be seen that the highest light scattering of GO is observed at the zeta potential of −17.29 mV, which is mainly owing to the ionization of oxygenated functional groups in a high polar solvent like water, and the pristine GO would assume slightly negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…27 Polymeric beads have been used to provide volume exclusion effect that leads to an effective continuous filler network in polymer matrix. [29][30][31][32] Grunlan et al 29 reported a significant improvement in electrical and thermal conductivity of polymer matrix with a low content of carbon nanotubes (CNT) using spherical polymer particles of poly(vinyl acetate). They claimed that the improved conductivity was attributed to the segregated network by the formation of CNT-CNT connection.…”
Section: Introductionmentioning
confidence: 99%
“…The thermally conductive nanoparticles were formed the segregated structure in the presence of polymer beads in the epoxy matrix using hot-press method. 32 The polymer beads were also utilized as a core template for coating a shell layer of multiwall carbon nanotubes (MWCNTs), then the embedded core-shell structure of MWCNTs@polymer beads resulted in thermal conductivity of 0.95 W m −1 K −1 at 1 wt% of MWCNTs loading. 25 To the best author's knowledge, most of researchers have been concentrating to improve the properties of 3D printed composites by loading higher amount of fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The polymer-based composites with various thermally conductive fillers are in high demand as thermal management materials because of their easy processability, low production cost, and lightweight. [6][7][8] In general, the thermally conductive composites are prepared by a random dispersion of the fillers in polymer matrix and the composites require a high filler loading to reach a high thermal conductivity. [9][10][11] However, the high filler loading leads to a deterioration of mechanical properties, the difficulty of processing, and heavyweight.…”
Section: Introductionmentioning
confidence: 99%